Chemical heat derived from rocket-borne WADIS-2 experiment - Mykhaylo Grygalashvyly; Boris Strelnikov; Irina Strelnikova; Markus Rapp; Franz-Josef Lübken; Corinna Schütt; Claudia Stephan; Martin Eberhart; Stefan Löhle; Stefanos Fasoulas (Earth, Planets and Space)
Abstract Chemical heating rates were derived from three of the most significant reactions based on the analysis of common volume rocket-borne measurements of temperature, atomic oxygen densities, and neutral air densities. This is one of the first instances of the retrieval of nighttime chemical heat through the utilization of non-emissive observations of atomic oxygen concentrations, obtained through in situ measurements, performed at the Andøya Space Center (69°N, 16°E) at 01:44:00 UTC on 5 March 2015. Furthermore, we determine the heating efficiency for one of the most significant reactions of atomic hydrogen with ozone and illustrate the methodology for such calculations based on known atomic oxygen and temperature. Subsequently, using ozone values obtained from satellite observations, we retrieved odd-hydrogens and total chemical heat. Finally, we compared the retrieved chemical heat with the heat from turbulent energy dissipation. Our findings reveal that the vertically averaged chemical heat is greater than the heat from turbulent energy dissipation throughout the entire mesopause region during nocturnal conditions. The heating rates of turbulent energy dissipation may exceed the chemical heating rates only in narrow peaks, several hundred meters wide. Graphical Abstract